Perbedaan Penafsiran Majelis Hakim Terkait Frase Muatan yang Melanggar Kesusilaan dalam Undang-Undang Informasi dan Transaksi Elektronik - Ferdinandus, Aisyah; Rifai, Anis (University of Merdeka Malang, 2024)
An analysis of judicial decisions regarding morality violations in Indonesia reveals several key conclusions reflecting the dynamics and interpretations of law in the digital context. Firstly, interpretations of morality under the Information and Electronic Transactions Law (ITE Law) tend to be limited to aspects of pornography and sexual exploitation, yet there is variation in interpretation by judicial panels, especially when the ITE Law does not provide a specific definition. The importance of concrete and contextual evidence is highlighted in assessing morality violations. Secondly, there is a push for harmonization between the ITE Law and the Criminal Code, particularly in the context of morality, to achieve consistency in law enforcement in the digital era. Thirdly, there is a need for legal clarification regarding the definition of morality under the ITE Law to ensure the consistency and relevance of legal interpretations in line with technological and societal developments. Judges emphasize the importance of considering privacy contexts in assessing morality violations, with an emphasis on the role of private spaces in setting boundaries for actions that violate moral norms. In conclusion, legal openness and clarity are crucial in addressing evolving challenges in the digital era for society, law enforcement, and the judiciary.